Peran Keluarga dan Masyarakat terhadap Pendidikan Perspektif Pendidikan Islam - Alfi Sukrina; Muhammad Ersyad Anshari; Muhiddinur Kamal; Januar Januar (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This article aims to explain the role of family and society in education. This research uses the literature study method which has the main sources from books, journals and other scientific articles. The data collected was analyzed using content analysis to make it easier for the author to filter the main ideas from various existing sources to be narrated into the focus of the study. The findings in this article: (1) The Role of Society in Education (2) Improving the Quality of Education (3) Government Responsibility for Education (4) Family Responsibility for Education.